1995
DOI: 10.1074/jbc.270.7.3239
|View full text |Cite
|
Sign up to set email alerts
|

c-Kit Ligand Mediates Increased Expression of Cytosolic Phospholipase A2, Prostaglandin Endoperoxide Synthase-1, and Hematopoietic Prostaglandin D2 Synthase and Increased IgE-dependent Prostaglandin D2 Generation in Immature Mouse Mast Cells

Abstract: We have examined the cytokine regulation of IgE-dependent prostaglandin (PG) D2 generation in mouse mast cells by assessing the changes in the levels of the transcript, translated protein, and activity of the enzymes involved in the synthesis of PGD2 from endogenous arachidonic acid. When mouse mast cells, derived by culture of bone marrow cells with WEHI-3 cell-conditioned medium as a source of interleukin (IL)-3 (BMMC), were cultured in recombinant ckit ligand (KL), sensitized with IgE, and stimulated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
119
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 130 publications
(125 citation statements)
references
References 68 publications
5
119
1
Order By: Relevance
“…These results suggest that arachidonic acid is produced and metabolized at the NE and ER. Murakami et al (41) reported that there is a linkage between cPLA 2 and cox-1 in c-kit ligand-primed, IgE-dependent PGD 2 synthesis in mouse mast cells. A linkage between cPLA 2 and cox-2 has also been suggested in monocytes and fibroblasts (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that arachidonic acid is produced and metabolized at the NE and ER. Murakami et al (41) reported that there is a linkage between cPLA 2 and cox-1 in c-kit ligand-primed, IgE-dependent PGD 2 synthesis in mouse mast cells. A linkage between cPLA 2 and cox-2 has also been suggested in monocytes and fibroblasts (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Mouse recombinant IL-3, IL-9, and IL-10 were produced by expression in insect cells, and their concentrations were determined as described (10,20). William Smith (Michigan State University, East Lansing, MI) supplied rabbit polyclonal antiserum to PGHS-2, and Jim Clark (Genetics Institute, Boston, MA) supplied rabbit polyclonal antiserum to cPLA 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Reagents-Mouse recombinant KL and IL-3 were expressed by the infection of Sf9 insect cells with recombinant baculovirus (58). Rat mAb 2.4G2 anti-mouse Fc␥RIIB/III, mouse IgE mAb IgE-3 anti-trinitrophenyl (TNP), FITC-rat mAb R35-72 anti-mouse IgE, FITC-rat mAb 2B8 anti-mouse Kit, and FITC-rat IgG 2b were purchased from Pharmingen.…”
Section: Methodsmentioning
confidence: 99%